The Impact of International Organization of Securities Commissions (IOSCO) Principles on Sukuk - Suhaili bin Haji Momin; Hakimah Yaacob (Journal of Indonesian Comparative of Syari'ah Law, 2025)
In this century, local financial systems have faced unprecedented turmoil since the Global Financial Crisis (GFC) 2008, exacerbated by the COVID-19 pandemic even more severe according to several indicators. Regulatory failures linked to market failures provide the economic rationale for interventions, including additional regulations, though these often result in higher costs and lower benefits than anticipated, leading to net harmful effects. The International Organization of Securities Commissions (IOSCO) serves as a global partnership of regulatory bodies to establish standards for efficient, orderly, and fair markets. This study analyzes the impact of IOSCO Core Principles on the development of Sukuk—Shariah-compliant bonds that have grown rapidly over the past two decades. While flexible for conventional markets, their application to Shariah securities remains uncertain. Using a comprehensive analytical approach, this research evaluates the compatibility of IOSCO principles with Islamic financial products, demonstrating that structural adjustments and adaptive regulations can enhance the credibility, transparency, and sustainable growth of Sukuk. The findings emphasize coordination among regulators for an inclusive supervisory framework that integrates Shariah principles with global standards, promoting the fair integration of Islamic financial markets into the global system.